THE INFLUENCES OF SCANNING STRATEGY AND READING INTEREST TOWARDS THE EIGHTH GRADE STUDENTS’ READING COMPREHENSION ON LABEL TEXTS OF PGRI JUNIOR HIGH SCHOOL 1 OF PALEMBANG - Desprayoga; Baginda; Mulyadi (Esteem Journal of English Education Study Programme, 2024)
The writer used a strategy calls scanning strategy to solve students’ problems in reading comprehension. Scanning Strategy and reading interest give a significant influence on the students’ reading comprehension achievement especially for students who havea low reading interest. The teacher of English should be more creative to choose the technique for students.The main problem of this study was formulated as follows: ‘Was there any significant difference in reading comprehension achievement between the eighth grade students who had high reading interest taught by using scanning strategy and those who were taught by using conventional technique at Junior High School PGRI 1 of Palembang, was there any significant difference in reading comprehension achievement between the eighth grade students who had low reading interest taught by using scanning strategy and those who were taught by using conventional technique at Junior High School PGRI 1 of Palembang, was there any significant difference in reading comprehension achievement between the eighth grade students taught by using scanning strategy who had high and low reading interest at Junior High School PGRI 1 of Palembang, was there any significant difference in reading comprehension achievement between the eight grade students taught by using conventional technique who had high and low reading interest at Junior High School PGRI 1 of Palembang and were there any interaction effects of scanning strategy and students’ reading interest towards the eighth grade students’ reading comprehension achievement at Junior High School PGRI 1 of Palembang. This study used experimental research. method. The subjects of this study were eighth grade students of PGRI Junior High School 1 of Palembang. While the object of this research is the used 2 x 2 (two by two) factorial designs because there were two factors (Scanning Strategy and reading Interest) and two levels (low and High Reading Interest).